The Transformative Impact of ASICs across Industries: A Technical Analysis - Anubhav Mangla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Application-Specific Integrated Circuits (ASICs) have emerged as a transformative technology in the semiconductor industry, revolutionizing various sectors, including healthcare, retail, agriculture, and computing. This comprehensive article explores the technical architecture, industry-specific implementations, challenges, and future directions of ASIC technology. The article examines the evolution of ASIC design methodologies and their impact on performance optimization, power efficiency, and manufacturing processes. It further investigates the integration of artificial intelligence in design automation, verification processes, and optimization techniques while addressing the complexity challenges in modern ASIC development. The article also highlights the significant advancements in industry-specific applications, from medical imaging systems to edge computing implementations, demonstrating the versatile impact of ASICs across different domains.